A BODIPY-Based Probe Enables Fluorogenicity via Thiol-Dependent Modulation of Fluorophore Aggregation - Tak Ian Chio; Akiva J. Grimaldi; Thomas I. Radford; Susan L. Bane (Molecules, 2022)
Given the popular usage of BODIPY fluorophores in biological research, their propensity to aggregate in aqueous solution and impact their spectroscopic properties arguably warrants more attention. The probe under study herein serves as a case in point. A para-maleimide-substituted meso-phenyl BODIPY (p-MB) had previously been characterized in organic media, where its inherently high fluorescence ruled out its fluorogenic potential. Here, we have found that in aqueous solution, p-MB behaves differently, exhibiting a much-reduced fluorescence as a result of aggregation-caused quenching (ACQ). Additionally, p-MB is capable of responding to complementarily reactive substrates, including thiols and TCEP, to generate a substantial turn-on signal. The fluorescence restoration is largest when it reacts with those containing adjacent ionizable groups. By being part of a polar conjugate, p-MB assumes a disaggregated form, circumventing ACQ and unleashing up to ~1000-fold fluorescence enhancement through apparent disaggregation-induced emission (DIE). While our results support DIE as the turn-on mechanism, we found that the reactivity of the probe is much lower when it is given time to form stable aggregates. Therefore, contrary to the conventional depiction that a DIE probe works by dispersing from preformed aggregates to react with the target, our results suggest that it functions via a target-mediated inhibition of probe aggregation. Altogether, our work highlights the aggregation issue often faced by BODIPY-based probes and demonstrates how that can be exploited for turn-on sensing application. Furthermore, it reconstructs a different pathway for the DIE mechanism.